Modeling of the load of a water-reflecting shield of a floating mobile machine - Tarichko V.I.; Shalupina.P.I.; Emelianova G.A. (Научно-технический вестник Брянского государственного университета)
Floating mobile machines have become widespread as a base for the creation of transport and technological complexes. They can also be used as the chassis of base stations of mobile transport and reloading rope complexes. One of the most important components ensuring safe navigation is a wave-reflecting shield that increases buoyancy and prevents the car from being flooded by an oncoming wave. The article discusses the methodology of modeling and the results of calculating the water-reflecting shield of a floating mobile machine manufactured by JSC «BAZ».